Amines tuned controllable carbonylation for the synthesis of γ-lactones and 1,4-diones - Yuanrui Wang; Youzhi Xu; Xin Qi; Le-Cheng Wang; Chao Xu; Genping Huang; Xiao-Feng Wu (Nature Communications)
Abstract In divergent carbonylative transformations using identical starting substrates, ligand-assisted transition metal catalysis has dominated selectively controllable transformations. However, achieving precise control of CO insertion in transition-metal-free systems remains a challenge. Herein, we disclose a divergent radical tandem carbonylation of multi-substituted homoallylic alcohols for the synthesis of γ-lactones and 1,4-diones. Utilizing quinuclidine as an electron donor steers the reaction towards lactonization, whereas the employment of DIPEA results in the migration of the aryl group to the carbonyl carbon. The key to tune the chemoselectivity lies in the ability of tertiary amines with different structures to precisely control the form of the active carbonyl intermediate, thereby inducing two distinct reaction pathways. Mechanistic studies reveal that the tertiary amine not only serves as an electron-transfer mediator but also functions as a tuner to govern chemoselectivity. The insights obtained from this study offer valuable enlightenment for selectively obtaining two types of carbonyl compounds, both advancing the performance exploring of electron donors in EDA complexes, fostering selective carbonylation development.